2017
DOI: 10.3892/ol.2017.7716
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of radiation effects in two irradiated tumor spheroid models

Abstract: Multicellular spheroids have proven suitable as three-dimensional in vivo-like models of non-vascularized micrometastases. Unlike monolayer-based models, spheroids mirror the cellular milieu and the pathophysiological gradients inside tumor nodules. However, there is limited knowledge of the radiation effects at the molecular level in spheroids of human origin. The present study is a presentation of selected cell biological processes that may easily be analyzed with methods available at routine pathology labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 20 publications
2
33
0
Order By: Relevance
“…7,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] However, most studies focus on the development of the actual 3D model and, to the best of our knowledge, there are very limited 3D studies on PDAC treatment screening (chemotherapy and radiotherapy) with most studies conducted in 3D spheroids (cell aggregates). 14,32,[34][35][36][49][50][51][52] Generally, these studies report a higher resistance of PDAC to treatment in 3D when compared to 2D cultures, a trend which is in closer alignment with in vivo studies. 34,49,52 For example, Longati et al (2013) studied the impact of the chemotherapeutic drug Gemcitabine (GEM, 0-1 mM) on the viability of PDAC spheroids and observed a higher resistance of the spheroids to the drug, as compared to a 2D culture.…”
Section: Introductionsupporting
confidence: 57%
See 4 more Smart Citations
“…7,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] However, most studies focus on the development of the actual 3D model and, to the best of our knowledge, there are very limited 3D studies on PDAC treatment screening (chemotherapy and radiotherapy) with most studies conducted in 3D spheroids (cell aggregates). 14,32,[34][35][36][49][50][51][52] Generally, these studies report a higher resistance of PDAC to treatment in 3D when compared to 2D cultures, a trend which is in closer alignment with in vivo studies. 34,49,52 For example, Longati et al (2013) studied the impact of the chemotherapeutic drug Gemcitabine (GEM, 0-1 mM) on the viability of PDAC spheroids and observed a higher resistance of the spheroids to the drug, as compared to a 2D culture.…”
Section: Introductionsupporting
confidence: 57%
“…14,32,[34][35][36][49][50][51][52] Generally, these studies report a higher resistance of PDAC to treatment in 3D when compared to 2D cultures, a trend which is in closer alignment with in vivo studies. 34,49,52 For example, Longati et al (2013) studied the impact of the chemotherapeutic drug Gemcitabine (GEM, 0-1 mM) on the viability of PDAC spheroids and observed a higher resistance of the spheroids to the drug, as compared to a 2D culture. The same study also reported that chemo-resistance differed amongst different cell lines with PANC-1 showing a higher resistance to GEM in comparison to BxPC-3 and Capan-1, 7 days aer drug administration.…”
Section: Introductionsupporting
confidence: 57%
See 3 more Smart Citations